Prosocial Reward Learning in Children and Adolescents - Kwak, Youngbin; Huettel, Scott A. (Frontiers in Psychology, 2016)
Adolescence is a period of increased sensitivity to social contexts. To evaluate how social context sensitivity changes over development – and influences reward learning – we investigated how children and adolescents perceive and integrate rewards for oneself and others during a dynamic risky-decision-making task. Children and adolescents (N=75, 8-16 yrs) performed the Social Gambling Task (SGT, (Kwak et al., 2014)) and completed a set of questionnaires measuring other-regarding behavior. In the SGT, participants choose amongst four card decks that have different payout structures for oneself and for a charity. We examined patterns of choices, overall decision strategies, and how reward outcomes led to trial-by-trial adjustments in behavior, as estimated using a reinforcement-learning model. Performance of children and adolescents was compared to data from a previously collected sample of adults (N=102) performing the identical task. We found that that children/adolescents were not only more sensitive to rewards directed to the charity than self but also showed greater prosocial tendencies on independent measures of other-regarding behavior. Children and adolescents also showed less use of a strategy that prioritizes rewards for self at the expense of rewards for others. These results support the conclusion that, compared to adults, children and adolescents show greater sensitivity to outcomes for others when making decisions and learning about potential rewards.